Answer:
3x²-24x+x-8 = 0
Explanation:
Given the equation 3x² - 23x - 8 = 0, in order to split the middle term which is -23x, first we will need to multiply the coefficient of x² by the constant of the equation i.e 3×(-8) to give -24.
Then we will find two numbers such that if the two numbers are multiplied together, it will give -24 and if the same 2numbers are added together, it will give the coefficient of x in the function i.e -23.
The two numbers are therefore -24 and +1.
-24×+1 = -24
-24+1 = -23
The trinomial can then be rewritten as thus;
3x²(-24x+x)-8 = 0
Note that the -23x has been splitted into -24x and +x